(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
The article presents a comparative analysis of the concept of freedom in Eastern and Western philosophical thought. It also explores the views of Eastern and W estern philosophers on freedom. The role of freedom in Eastern and Western societies is examined